Negotiating Digital Technology and Religious Autonomy among Madrasah Students in Tanjung Morawa, Indonesia - Melika Debiyana Putri; Nazwa Aidilia Octa Mevia; Yunanda Rizki Sitompul; Alifya Aisya Widjayani; Umar Mukhtar Siregar (Al Hikmah, 2026)
The increasing use of smartphones and digital religious applications has transformed how young Muslims access religious information and organize daily worship. This study examines patterns of digital technology use and religious autonomy among ninth-grade students at MTs Nurul Iman Tanjung Morawa. Religious autonomy refers to students’ ability to initiate worship, regulate device use during religious activities, and critically evaluate online religious information. The study employed a quantitative descriptive survey supported by open-ended responses. Data were collected from 60 students using a structured questionnaire consisting of Likert-scale items on technological use and religious autonomy. Quantitative data were analyzed through mean scores and percentage distributions, while narrative responses were categorized thematically. The findings show that students rely considerably on smartphones for accessing religious information, reflected in a mean score of 3.68 for seeking religious answers online. However, smartphone use during worship received a low mean score of 1.85. Indicators of religious autonomy were generally high, including worship without reminders, concentration during prayer, verification of online religious information, and the ability to distinguish credible from misleading content. Most respondents viewed smartphones as useful for accessing the Qur’an, prayer schedules, and religious learning materials, although some acknowledged that notifications and social media could cause distraction. These findings suggest that digital technology does not automatically weaken religious autonomy. Instead, students negotiate technology through self-regulation and digital boundaries. This study contributes to discussions on digital religion by showing how young Muslims integrate technology into religious life while maintaining personal responsibility and spiritual discipline.